Analisis Rekayasa Sub-System Penunjang di Salah Satu Sentra Pertanaman Padi di Agroekosistem Lahan Rawa, Kabupaten Tanjung Jabung Barat - Suharyon, Suharyon; BS, Busyra; Firdaus, Firdaus; Zubir, Zubir (Seminar Nasional Lahan Suboptimal, 2022)
Suharyon S, BS Busyra, Firdaus F, Zubir Z. 2022. Engineering analysis of supporting sub-systems in one of the rice cultivation centers in swampland agroecosystems, West Tanjung Jabung Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 189-198. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).In an effort to develop farming systems and rice plant institutions in an area, it is necessary to approach the relationship between farmer groups and other supporting institutions. With the establishment of good institutional cooperation, problems faced by farmers can be submitted and it is hoped that technology diffusion will occur through related institutions or institutions in the region. By empowering institutions that support the adoption of technology provided to farmer groups FSA (Farming System Analysis) in the form of cooperation, it will help solve the problems faced by farmers. Based on this thought, it is necessary to study the analysis of institutional engineering supporting rice farming technology. This activity was carried out in the village of Rawa Medang, Tanjung Jabung Barat Regency, with the aimed of finding effective treatments/interventions and increasing empowerment, as well as institutional cooperation to ensure the adoption of sustainable rice farming system technology. The methodology used in this activity is by applying the Participatory Research Appraisal (PRA) method, to explore the problems faced by rice farmers. Alternative interventions are the formation of several farmer groups or can be called Gapoktan which is named Joint Venture, a brief discussion about the rice farming system, seeing the urgent needs of farmer groups, and connecting them with supporting institutions. Based on the results of the PRA, the prioritized problems are (1) Acid sulphate soil, (2) Water management, (3), rat/planthopper pests, (4) Labor, (5) Capital, (6) Technical guidance for rice and rice plants. (7) Obtain subsidized fertilizer. The aimed is to find effective treatments/interventions and increase empowerment, as well as institutional cooperation to ensure the adoption of sustainable rice farming system technology.